Faktor-faktor yang Mempengaruhi Akuntabilitas Pengelolaan Alokasi Dana Desa di Desa Damarwulan Kecamatan Air Salek - Isna Khorul Azizah; Muhammad Titan Terzaghi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to determine the effect of community participation, village officials’ competence, information technology utilization, internal control systems, and clarity of budget targets on the accountability of village fund allocation management in Damarwulan Village, Air Salek District. The research used a quantitative method with a survey approach. The sample consisted of 37 respondents, including village officials, BPD members, and community representatives. Data analysis was conducted using multiple linear regression with SPSS software. The results show that community participation, competence of village officials, utilization of information technology, internal control systems, and clarity of budget targets have a positive and significant effect on the accountability of village fund allocation management. These findings suggest that enhancing these five factors can improve accountability in managing village funds, thereby promoting transparency and public responsibility at the village level.